The role of public service motivation and organizational culture for organizational commitment = Rola motywacji służby publicznej i kultury organizacyjnej dla zaangażowania organizacyjnego - Austen, Agata; Zacny, Bogna (Zielona Góra: Faculty of Economics and Management Press)
The aim of the our paper is to discuss the relationships between organizational culture, Public Service Motivation (PSM) and organizational commitment (OC). On the basis of literature review we formulated hypotheses presenting potential relationships between mentioned constructs.
Keywords: służba publiczna; wartości; motywacja; zaangażowanie organizacyjne; badania wielopoziomowe; values; Public Service Motivation; organizational culture; organizational commitment; multilevel research